2019
DOI: 10.1017/cts.2019.413
|View full text |Cite
|
Sign up to set email alerts
|

Identifying strategies to promote team science in dissemination and implementation research

Abstract: AbstractIntroduction:Scientific endeavors are increasingly carried out by teams of scientists. While there is growing literature on factors associated with effective science teams, little is known about processes that facilitate the success of dissemination and implementation (D&I) teams studying the uptake of healthcare innovations. This study aimed to identify strategies used by D&I scienti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 60 publications
1
26
0
Order By: Relevance
“…Our study identified the importance of effective communication and leadership across crossdisciplinary teams with health economists. These findings were consistent with a past study, which found that successful team science in implementation research was fostered when there were clear expectations and roles in conducting research, effective communication was promoted and modeled, and there was a shared goal and mission across team members [15]. Indeed, implementation researchers are frequently tasked with forming and leading large teams, which include community practitioners and researchers from multiple disciplines such as medicine, engineering, biostatistics, psychology, social work, anthropology, and economics.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our study identified the importance of effective communication and leadership across crossdisciplinary teams with health economists. These findings were consistent with a past study, which found that successful team science in implementation research was fostered when there were clear expectations and roles in conducting research, effective communication was promoted and modeled, and there was a shared goal and mission across team members [15]. Indeed, implementation researchers are frequently tasked with forming and leading large teams, which include community practitioners and researchers from multiple disciplines such as medicine, engineering, biostatistics, psychology, social work, anthropology, and economics.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, implementation researchers are frequently tasked with forming and leading large teams, which include community practitioners and researchers from multiple disciplines such as medicine, engineering, biostatistics, psychology, social work, anthropology, and economics. As opposed to learning each of these fields, implementation researchers can focus on gaining expertise in best practices in team science [14,15,23]. Many of the skills that facilitate other research partnerships can help to promote successful collaborations with health economists, including learning the "language" used in the field and clarifying that there is a shared understanding across researchers in terms of roles, expectations, and incentives.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Hwang et al 5 propose utilization of novel implementation science methodologies to advance health in the US and worldwide, while Yousefi et al 6 discuss interactions between health equity research and D&I science, underlying the importance of translational research with the focus on equitable D&I. Bennett et al highlighted a need for research integration into Learning Health Systems (LHS). 7 Aarons et al 8 and Dolor et al 9 examined opinions of D&I researchers and CTSA leaders to identify strategies that could promote team science and improve population health. The importance of partnerships between academic and public health systems and organizations is examined by both Kilbourne et al 10 and Towfighi et al 11 This is further explored in terms of a broader engagement of specific participants, including stakeholder and workforce related issues.…”
Section: Broad Themes From Papers Published In This Jcts Special Issumentioning
confidence: 99%